2010
DOI: 10.4097/kjae.2010.59.s.s41
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis after laparoscopic radical nephrectomy -A case report-

Abstract: Rhabdomyolysis is a rare but potentially lethal clinical syndrome that results from acute muscle fiber necrosis with leakage of muscle constituents into blood. This devastating disease could be due to muscle compression caused by urologic positioning for a lengthy nephrectomy. In this regard, laparoscopic renal surgery may be a risk for the development of rhabdomyolysis. This phenomenon of massive muscle necrosis can produce secondary acute renal failure. The risk factors have to be managed carefully during an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…[12] RM can also be seen as a result of compression of muscular tissue due to surgical positioning in prolonged laparoscopic or robotic surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] RM can also be seen as a result of compression of muscular tissue due to surgical positioning in prolonged laparoscopic or robotic surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Post-operative RM can be observed after vascular, neurosurgical and more commonly urological interventions. Risk factors include age (40–50 years of age), male gender, high body mass index (BMI),[3] perioperative overhydration, prolonged surgery[4] and surgical positioning (flexed lateral decubitus position and STP).…”
Section: Introductionmentioning
confidence: 99%
“…Karcher et al [ 7 ] report the case of an obese patient who developed rhabdomyolysis with ARF and hepatic dysfunction. Kim et al [ 12 ] and Park et al [ 13 ] also observed a marked elevation of AST and ALT. The mechanisms for liver dysfunction have not yet been elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…Lumbar plexopathy can occur as the result of direct trauma to the lumbar plexus, space-occupying lesions in the peritoneal cavity, complications after aortic surgery, and metabolic diseases [ 1 , 2 ]. Patients who undergo surgery under general anesthesia or regional anesthesia in the lateral decubitus, prone, or lithotomy positions experience complications that damage the soft tissues of the muscles or nerves [ 3 - 6 ]. There have been reports of patients who underwent a nephrectomy in the lateral decubitus position, where severe pressure on the opposite paraspinal muscles or gluteal muscles during surgery induced rhabdomyolysis [ 3 , 7 ].…”
mentioning
confidence: 99%
“…Patients who undergo surgery under general anesthesia or regional anesthesia in the lateral decubitus, prone, or lithotomy positions experience complications that damage the soft tissues of the muscles or nerves [ 3 - 6 ]. There have been reports of patients who underwent a nephrectomy in the lateral decubitus position, where severe pressure on the opposite paraspinal muscles or gluteal muscles during surgery induced rhabdomyolysis [ 3 , 7 ]. We report a patient who underwent a nephrectomy in the lateral decubitus position, experienced injury in the opposite paraspinal and iliopsoas muscles, and also evidenced lumbar plexopathy.…”
mentioning
confidence: 99%